Bullying: dimensões psicológicas no desenvolvimento moral - Tognetta, Luciene Regina Paulino [UNESP] (2013)
Understanding and assessing the extent of psychological mechanisms that operate in actions of specific violence acts such as bullying can contribute to the discussion of educational interventions that promote moral education as desired by educational institutions. The current research aimed toD correlateD this form of violence called bullying to representations of the self and even to the ways in which the subjects self-regulate themselves in hypothetical situations which pose the problem, thus identifying their moral commitments or non-commitments. The procedures followed to check the presence of these correlationsDindicate that subjects whose self-representations are individualistic are less morally committed and more likely to be perpetrators in bullying situations. This shows that more than a social problem, the issues of coexistence should be treated from a moral perspective.